Balancing climate and development goals. (15th December 2020) - Duan, Lei; Moreno-Cruz, Juan; Caldeira, Ken
Abstract: Decarbonizing the energy system is a major challenge facing the richest countries, whereas provision of energy services is a major challenge facing the poorest countries. What would be the climate consequences if only richer countries focus on decarbonization, and only poorer countries focus on provision of energy services? To address this question, we create future scenarios in which carbon dioxide (CO2 ) emissions increase according to a historical trend and then start to decline only when countries reach specified income levels. In our central case, we assume that when countries start to decarbonize, they reduce emissions at 2% yr −1 . With this assumption and if all countries begin to decarbonize in 2020, the world would be expected to warm by 2.0 °C relative to pre-industrial times. If countries begin to decarbonize only when their per capita gross domestic product (GDP) exceeds $10 000, there would be less than 0.3 °C of additional warming. Yet over half the world's population currently lives in countries below such an income threshold, and continued direct CO2 emissions by people who live in these countries, while they remain underdeveloped, would increase global average temperature rise by 14% relative to the case, in which all people begin to decarbonize in 2020. The primary concern of developments driven by fossil fuels in lower income countries might relate to issues such as the technological lock-in to high-emission technologies.